GIS/Remote sensing techniques for resource management and biodiversity protection in mountainous regions - All, John (Botanica Orientalis: Journal of Plant Science, 2010)
Biodiversity protection in mountainous regions requires effective fact-driven resource management techniques. Geoinformatic tools including GIS and remote sensing can be integrated to provide regional-scale data products across time for use in strategic and management level policymaking. Several principles are discussed to ensure that geoinformatics data and analysis can effectively contribute to resource management by clarifying issues and minimizing misinterpretation. A case study in the Chilean Andes elucidates these principles. Biological impacts of recent climate changes have not been equal across different ecosystems and stable forest ecosystems provide the best response to climate change. Geoinformatics is used to differentiate functional ecological groups and evaluate long-term resilience to climate change. Key-words: Chilean Andes; climate change; mountain ecosystems; geoinformatics; vegetation. DOI: 10.3126/botor.v6i0.2916 Botanica Orientalis - Journal of Plant Science (2009) 6: 93-99